Daily level predictors of impaired driving behaviors in young adults: Protocol design for utilizing daily assessments. - Brittney A Hultgren; Katarina Guttmannova; Christine M Lee; Daniela Acuna; Rachel L Cooper; Jason R Kilmer; Jennifer M Cadigan; Brian H Calhoun; Mary E Larimer (PLoS ONE, 2022)
Background Motor vehicle crashes remain a leading cause of death among young adults (ages 18-25) in the United States. Many drivers implicated in these crashes are under the influence of alcohol, cannabis, or the simultaneous use of alcohol and cannabis. Extremely limited research has assessed impaired driving behaviors and their predictors at the daily level. Perceived norms and motives to use substances have empirical support suggesting they may impact impaired driving-related behavior. Novel approaches to assess these associations at the daily level are needed and may inform future intervention and prevention programs. Objective The goal of the current study is to utilize electronic daily assessments to assess driving under the influence of alcohol, cannabis, or simultaneous use and riding with a driver impaired by these substances to assess variability and predictors of these impaired driving-related behaviors at the daily level. This present manuscript details a protocol, measures, and a plan of analyses to assess how within-person differences in perceived norms and motives to use are associated with the likelihood of engaging in impaired driving-related behaviors. Methods Participants include young adults in Washington State who report simultaneous use in the past month and either driving under the influence of alcohol, cannabis, or simultaneous use, or riding with a driver under the influence of both substances in the past 6 months. Individuals who verify their identity and meet eligibility requirements will complete a baseline assessment after which they will be scheduled for training on the daily assessment procedure via Zoom. Next, they will be invited to complete daily surveys on Thursday, Friday, Saturday, and Sunday every other week for 6 months and a 6-month follow up assessment. Analyses will utilize multilevel models with days nested within individuals. Results The study is currently recruiting participants. A total of 192 participants have been recruited and 100 have completed the study protocol. Data collection is expected to be completed in Fall 2022. Conclusions This study utilizes a novel design to assess impaired driving and predictors at the daily level among young adults at high risk of impaired driving-related behaviors. Findings will provide unique data that will shape the knowledge base in the field of social science and public health substance use research and that may be helpful for future prevention and intervention efforts on impaired driving.